Drawing the line between adaptation and development: a systematic literature review of planned adaptation in developing countries. (14th July 2016) - Sherman, Mya; Berrang‐Ford, Lea; Lwasa, Shuaib; Ford, James; Namanya, Didacus B.; Llanos‐Cuentas, Alejandro; Maillet, Michelle; Harper, Sherilee; IHACC Research Team,
Abstract : Climate change adaptation is increasingly considered an urgent priority for policy action. Billions of dollars have been pledged for adaptation finance, with many donor agencies requiring that adaptation is distinct from baseline development. However, practitioners and academics continue to question what adaptation looks like on the ground, especially in a developing country. This study examines the current framing of planned adaptation amidst low socioeconomic development and considers the practical implications of this framing for adaptation planning. Three overarching approaches to planned adaptation in a developing country context emerged in a systematic review of 30 peer‐reviewed articles published between 2010 and 2015, including: (1) technocratic risk management, which treats adaptation as additional to development, (2) pro‐poor vulnerability reduction, which acknowledges the ability of conventional development to foster and act as adaptation, and (3) sustainable adaptation, which suggests that adaptation should only be integrated into a type of development that is socially and environmentally sustainable. Over half of 'sustainable adaptation' articles in this review took a critical adaptation approach, drawing primarily from political ecology and postdevelopment studies, and emphasizing the malleability of adaptation. The reviewed articles highlight how the different framings of the relationship between adaptation and development result in diverse and sometimes contradictory messages regarding adaptation design, implementation, funding, monitoring, and evaluation. This review illustrates the need to continually interrogate the multiple framings of adaptation and development and to foster a pragmatic and pluralistic dialogue regarding planned adaptation and transformative change in developing countries. WIREs Clim Change 2016, 7:707–726. doi: 10.1002/wcc.416 This article is categorized under: Vulnerability and Adaptation to Climate Change > Learning from Cases and Analogies Climate and Development > Knowledge and Action in Development